MINIMIZING ON TIME DELIVERY OF GOODS WITH GREEDY ALGORITHM - Yoanita Tungga; Irfan, SKom, MM Irfan, SKom, MM (Jurnal Sistem Informasi, 2000)
Graph theory was historically born  in the 18th century, then a mathematician Euler Leonhart Euler solved the bridge problem. Graph Theory itself is one branch of mathematics. Along with the progress of computerization today, Graph Theory is widely used in various science and technology, let alone on the hardware and computer software, research and operations, marketing problems, economic problems.